2004
DOI: 10.1097/01.tp.0000118409.92769.fa
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia Correlates With the Presence or Development of Chronic Graft-Versus-Host Disease in Children

Abstract: Finding predictors of chronic graft-versus-host disease (cGVHD) in children would be extremely useful. Because of recent data suggesting that cGVHD may be a Th-2-mediated process, a theoretical foundation linking eosinophilia and cGVHD exists. While an association between eosinophilia and cGVHD has been described in adults, it has never been described in children. We studied 53 patients that received allogeneic hematopoietic stem cell transplants (SCT) between 1999 and 2002. Ten (19%) of these patients develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 11 publications
0
35
1
Order By: Relevance
“…10,19,20 In our study, patients with skin cGVHD had a significantly higher mean peak peripheral eosinophil count than control patients, with a mean time of onset of eosinophilia of 54 days before the symptoms of cGVHD. Patients with sclerotic cGVHD were more likely to have preceding eosinophilia than those with nonsclerotic disease.…”
Section: Demographicsmentioning
confidence: 75%
“…10,19,20 In our study, patients with skin cGVHD had a significantly higher mean peak peripheral eosinophil count than control patients, with a mean time of onset of eosinophilia of 54 days before the symptoms of cGVHD. Patients with sclerotic cGVHD were more likely to have preceding eosinophilia than those with nonsclerotic disease.…”
Section: Demographicsmentioning
confidence: 75%
“…Eosinophilia in the blood and tissue is a common feature of GvHD and contributes to the allogeneic response, as revealed in investigations of GvHD in animal models (73,74). Studies have shown that eosinophilia is a predictor for acute and chronic GvHD (75,76). However, the prognostic significance remains controversial, as some studies have shown a favorable correlation with survival (77)(78)(79) and others have shown the opposite effect (80).…”
Section: Graft-versus-host Diseasementioning
confidence: 98%
“…A number of studies, mostly in adults, have shown that thrombocytopenia at the time of chronic GVHD diagnosis confers a poor prognosis (Sullivan et al, 1988a;Akpek et al, 2001b). Eosinophilia is often seen in children with chronic GVHD and sometimes precedes the occurrence of chronic GVHD (Jacobsohn et al, 2004). Eosinophilia usually resolves with adequate systemic treatment of GVHD.…”
Section: Haematopoietic Systemmentioning
confidence: 99%